Correlations between a Smoking Habit and Teeth, Gums and Lips Discoloration Issues on Active Smoker - Caecielia Makaginsar; Yuniarti Yuniarti; Siska Nia Irasanti; Aliya Salsabila; Tannia Kusumawardhani (Universitas Islam Bandung, 2022)
According to the Central Statistics Agency, the percentage of smokers among Indonesians aged 15 years is relatively high. It was 32.20%, 29.03%, and 28.69%, in 2018, 2019, and 2020 respectively. Cigarettes contain tar that changes into a solid and builds up colored plaque when entering the mouth. Perpetual cigarette smoke causes brown pigmentation on the mucosa, known as smoker's melanosis. Smoker's melanosis is abundant in gums and lips. This study's objective was to analyze the correlations between a smoking habit with teeth, gums, and lips discoloration in an active smoker. This study was an observational analysis with a survey approach from January to May 2021 in Bandung. The sample was 100 males, consisting of 38 active smokers and 62 non-smokers as a comparison group. Data were analyzed by Pearson and Spearman test. This study shows a significant correlation between smoking habit and teeth discoloration (p=0.01), also shows a statistically significant correlation between a smoking habit and gum discoloration (p=0.00), and there is a significant correlation (p=0.00) between a smoking habit and lips discoloration. In conclusion, there is a correlation between a smoking habit and teeth, gums, and lips discoloration.